Will accelerated soil development be a driver of Arctic Greening in the late 21st century?. Issue 1 (25th November 2021) - Doetterl, Sebastian; Alexander, Jake; Fior, Simone; Frossard, Aline; Magnabosco, Cara; van de Broek, Marijn; Westergaard, Kristine Bakke
Abstract: Take‐Home Message Climate warming is transforming the Arctic at an unprecedented rate with previously barren and sparsely vegetated landscapes undergoing "greening". We postulate that the observed vegetation changes throughout the Arctic are not only tied to warming, but to changes in soil properties and their impacts on plants and soil microbial communities. A key to understanding extent and patterns of greening of formerly sparsely vegetated Arctic environments will be to unravel the interactions between the biosphere and the role of soil genesis.